2021
DOI: 10.1038/s41598-021-86458-x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione ethyl ester reverses the deleterious effects of fentanyl on ventilation and arterial blood-gas chemistry while prolonging fentanyl-induced analgesia

Abstract: There is an urgent need to develop novel compounds that prevent the deleterious effects of opioids such as fentanyl on minute ventilation while, if possible, preserving the analgesic actions of the opioids. We report that L-glutathione ethyl ester (GSHee) may be such a novel compound. In this study, we measured tail flick latency (TFL), arterial blood gas (ABG) chemistry, Alveolar-arterial gradient, and ventilatory parameters by whole body plethysmography to determine the responses elicited by bolus injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 142 publications
6
44
1
Order By: Relevance
“…Consistent with previous reports ( Jenkins et al, 2021 ; Seckler et al, 2022 ), each injection of fentanyl in vehicle-infused rats elicited substantial, relatively short-lived increases in occurrence of non-eupneic breaths, as demonstrated by the increases in NEBI and NEBI/f R . Based on the known effects of opioids on breathing patterns ( Zutler and Holty, 2011 ; Nagappa et al, 2017 ), it is likely that most non-eupneic breathing consists of breath-holds (apneas) although other events, such as type 1 and type 2 sighs, may have occurred.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous reports ( Jenkins et al, 2021 ; Seckler et al, 2022 ), each injection of fentanyl in vehicle-infused rats elicited substantial, relatively short-lived increases in occurrence of non-eupneic breaths, as demonstrated by the increases in NEBI and NEBI/f R . Based on the known effects of opioids on breathing patterns ( Zutler and Holty, 2011 ; Nagappa et al, 2017 ), it is likely that most non-eupneic breathing consists of breath-holds (apneas) although other events, such as type 1 and type 2 sighs, may have occurred.…”
Section: Discussionsupporting
confidence: 92%
“…Antinociception status in unanesthetized rats was determined by a radiant heat tail-flick latency (TFL) assay, as detailed previously ( Lewis et al, 1991 ; Henderson et al, 2014 ; Gaston et al, 2021 ; Jenkins et al, 2021 ). Prior to administration of fentanyl, the rats were allowed to crawl inside a canvas garden glove and lightly restrained within the glove to allow for the thermal withdrawal latencies to be determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that l -cysteine ethyl ester ( Mendoza et al, 2013 ), glutathione ethyl ester ( Jenkins et al, 2021 ), and d -cystine methyl and ethyl esters ( Gaston et al, 2021 ) rapidly reverse the negative effects of opioids, such as morphine and fentanyl, on breathing, Alveolar-arterial gradient (i.e., the index of gas exchange within the lungs) and arterial blood-gas (ABG) chemistry while not reducing opioid analgesia. Since these reduced and oxidized thiol esters block the negative effects of opioids on breathing and because the potent reducing agent N-acetyl- l -cysteine methyl ester does not affect opioid-induced depression of breathing ( Baby et al, 2021 , it is unlikely that the thiol esters exert their effects by altering the redox state of cells involved in the effects of opioids on breathing.…”
Section: Introductionmentioning
confidence: 99%
“…In a third study, in awake rats, the investigators show that pretreatment with glutathione ethyl ester offsets fentanyl-induced respiratory depression through effects on respiratory rate and tidal volume, and consequently stabilized breathing and enhanced analgesia. 51 In summary, these studies show that ethyl esters increase respiratory rate and sometimes also tidal volume, and that the increase is sustained during moderate opioid-induced respiratory depression, offsetting the opioid effect on respiratory rate. Finally, in awake and isoflurane-anesthetized rats, pretreatment with the antioxidant Tempol (4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl) prevented fentanyl-induced respiratory depression, while the potent antioxidant N-acetyl-L-cysteine methyl ester was without effect.…”
Section: Antioxidantsmentioning
confidence: 71%